Integrated Management of Childhood Illnesses strategy: compliance with referral and follow-up recommendations in Gezira State, Sudan - Al Fadil Sumaia Mohammed; Abd Alrahman Samira Hamid; Cousens Simon; Bustreo Flavia; Shadoul Ahmed; Farhoud Suzanne; El Hassan Samia Mohamed (The World Health Organization, 2003)
OBJECTIVES: To determine the extent to which families follow referral and follow-up recommendations given in accordance with the Integrated Management of Childhood Illnesses (IMCI) strategy and the factors that influence families' responses to such recommendations. METHODS: Children aged 2 months-5 years who presented to an IMCI-trained health worker in Massalamia Health Area, Sudan, were recruited. Children with an IMCI classification that indicated the need for referral or follow-up were traced to determine whether the family complied with the referral or follow-up recommendation. Caretakers were interviewed to find out why they had or had not complied. Focus group discussions were held with health workers, caretakers, and community members. FINDINGS: Overall, 5745 children were enrolled. Of these, 162 (3%) were considered to be in need of urgent referral: 53 (33%) attended a hospital on the day of the referral, with a further 37 (23%) visiting the hospital later than the day of referral. About half of families cited cost as the reason for not visiting a hospital. A total of 1197 (21%) children were classified as needing follow-up. Compliance with a follow-up recommendation was 44% (529 children). Almost 165 (90%) of caretakers who were aware of and did not comply with follow-up, said they had not done so because the child was better. Compliance increased with the caretaker's level of education, if drugs were provided during the first visit, and if the follow-up period was short (2 or 5 days). CONCLUSION: In Massalamia - a resource-constrained environment in which IMCI implementation was well received by the community - only about half of children judged to be in need of urgent referral were taken for that care within 24 hours. Most children in need of follow-up received their first treatment dose in the health facility. This aspect of IMCI was commented upon favourably by caretakers, and it may encourage them to return for follow-up. Rates of return might also improve if return visits for children currently asked to return after 14 or 30 days were scheduled earlier.